Albania : Report on the Observance of Standards and Codes-Data Module, Response by the Authorities, and Detailed Assessments Using the Data Quality Assessment Framework. (IMF Staff Country Reports; Country Report, 2006)
Albania was among the first countries to participate in the General Data Dissemination System (GDDS), posting its metadata on the Dissemination Standards Bulletin Board. Its metadata have been used as a model by other countries participating in the GDDS. Recommendations to increase further Albania's adherence to internationally accepted statistical practices, and enhance the analytical usefulness of its statistics include additional staff resources, expanding and improving surveys, implementing measures to minimize errors in commercial banks' reporting, and to speed up processes in addressing these errors.